Phase I Study of the Indoleamine 2,3-Dioxygenase 1 (IDO1) Inhibitor Navoximod (GDC-0919) Administered with PD-L1 Inhibitor (Atezolizumab) in Advanced Solid Tumors - Jung, Kyung Hae; LoRusso, Patricia; Burris, Howard; Gordon, Michael; Bang, Yung-Jue; Hellmann, Matthew D; Cervantes, Andrés; Ochoa de Olza, Maria; Marabelle, Aurelien; Hodi, F Stephen; Ahn, Myung-Ju; Emens, Leisha A; et al. (Clinical cancer research, 2019)
IDO1 induces immune suppression in T cells through l-tryptophan (Trp) depletion and kynurenine (Kyn) accumulation in the local tumor microenvironment, suppressing effector T cells and hyperactivating regulatory T cells (Treg). Navoximod is an investigational small-molecule inhibitor of IDO1. This phase I study evaluated safety, tolerability, pharmacokinetics, and pharmacodynamics of navoximod in combination with atezolizumab, a PD-L1 inhibitor, in patients with advanced cancer. The study consisted of a 3+3 dose-escalation stage ( = 66) and a tumor-specific expansion stage ( = 92). Navoximod was given orally every 12 hours continuously for 21 consecutive days of each cycle with the exception of cycle 1, where navoximod administration started on day -1 to characterize pharmacokinetics. Atezolizumab was administered by intravenous infusion 1,200 mg every 3 weeks on day 1 of each cycle. Patients ( = 157) received navoximod at 6 dose levels (50-1,000 mg) in combination with atezolizumab. The maximum administered dose was 1,000 mg twice daily; the MTD was not reached. Navoximod demonstrated a linear pharmacokinetic profile, and plasma Kyn generally decreased with increasing doses of navoximod. The most common treatment-related AEs were fatigue (22%), rash (22%), and chromaturia (20%). Activity was observed at all dose levels in various tumor types (melanoma, pancreatic, prostate, ovarian, head and neck squamous cell carcinoma, cervical, neural sheath, non-small cell lung cancer, triple-negative breast cancer, renal cell carcinoma, urothelial bladder cancer): 6 (9%) dose-escalation patients achieved partial response, and 10 (11%) expansion patients achieved partial response or complete response. The combination of navoximod and atezolizumab demonstrated acceptable safety, tolerability, and pharmacokinetics for patients with advanced cancer. Although activity was observed, there was no clear evidence of benefit from adding navoximod to atezolizumab.